2022
DOI: 10.1177/15589447221075669
|View full text |Cite
|
Sign up to set email alerts
|

Does Time to Imaging and Surgery for Distal Radius Fractures Vary based on Geographic Socioeconomic Disadvantage?

Abstract: Background: While disparities in aspects of distal radius fracture (DRF) management and orthopedics at large have been studied, disparities in time to DRF evaluation and treatment are unknown. We sought to determine if geographic socioeconomic disadvantage is associated with time to imaging in the emergency department (ED) and time to surgery for DRFs. Methods: We performed a time-to-event analysis of 105 patients undergoing DRF surgery after ED triage within our hospital system between January 1, 2015, and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(80 reference statements)
0
6
1
Order By: Relevance
“…Although other studies have established differences in DRF treatment by socioeconomic status, the present study uniquely contributes to the literature by using an RDD to ascertain whether entry to Medicare was associated with greater parity in intensive management . The findings differed from other studies that used this quasi-experimental strategy to investigate Medicare eligibility and health equity.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Although other studies have established differences in DRF treatment by socioeconomic status, the present study uniquely contributes to the literature by using an RDD to ascertain whether entry to Medicare was associated with greater parity in intensive management . The findings differed from other studies that used this quasi-experimental strategy to investigate Medicare eligibility and health equity.…”
Section: Discussioncontrasting
confidence: 58%
“…Although other studies have established differences in DRF treatment by socioeconomic status, the present study uniquely contributes to the literature by using an RDD to ascertain whether entry to Medicare was associated with greater parity in intensive management. [10][11][12]56,57…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] This is particularly important, as it has previously been shown that there are disparities in time to surgery for DRF in patients with geographic socioeconomic disadvantage. 10 There exists substantial literature on disparities for patients undergoing arthroplasty as well as spinal surgery. Previous studies have shown increased hospital LOS, postoperative complications, and readmission rates in joint arthroplasty and spinal fusion for minority patients when compared to White patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 Our own work has demonstrated disparities in timing of distal radius fracture surgery in more disadvantaged groups. 3 The effects of these variables may very well explain the discrepancies in pain reported by the authors.…”
mentioning
confidence: 92%